2000
DOI: 10.1063/1.1322578
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of muscle hemoglobin oxygenation using near-infrared spectroscopy with correction for the influence of a subcutaneous fat layer

Abstract: The inhomogeneity of tissue structure greatly affects the sensitivity of tissue oxygenation measurement by reflectance near-infrared spectroscopy. In this study, we investigated the influence of a fat layer on muscle oxygenation measurement by in vivo tests and Monte Carlo simulation, and we propose a method for correcting the influence. In the simulation, a three-dimensional model consisting of the epidermis, dermis, fat, and muscle layers was used. In in vivo tests, measurement sensitivity was examined by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 17 publications
7
74
1
Order By: Relevance
“…This corresponds to an attenuation of the NIR signal by <10% of the assumed 0-mm fat layer thickness. 32 After the elimination of the effect of confounder factors, using stepwise multiple regressions, the relationship between BAT-d and BMI, %BF, and VFA was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to an attenuation of the NIR signal by <10% of the assumed 0-mm fat layer thickness. 32 After the elimination of the effect of confounder factors, using stepwise multiple regressions, the relationship between BAT-d and BMI, %BF, and VFA was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential sources of uncertainty in the measurements with NIRS are the unknown region investigated that can be only estimated, interference of adipose tissue thickness (Niwayama et al 2000), and relative contributions of Hb and Mb (Mancini et al 1994;Tran et al 1999). Most studies focus on Hb changes, since it has been reported that intracellular Mb accounts for less than 10% of the total NIRS signal (Grassi et al 2003).…”
Section: Measurement Limitationsmentioning
confidence: 99%
“…2) ), which is standard procedure . By expressing mVO 2 in this manner, potential diVerences in subcutaneous fat between muscles, which greatly aVect NIRS measurement sensitivity (Niwayama et al 2000;van Beekvelt et al 2001), are accounted for. Maximal deoxygenation is deWned as the absolute diVerence in [O 2 Hb] (and [HHb]) when virtually all O 2 Hb is converted into HHb.…”
Section: Near-infrared Spectroscopy (Nirs)mentioning
confidence: 99%